2022
DOI: 10.3390/su142215436
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation as an Enabler to Become More Efficient in Sustainability: Evidence from Five Leading Companies in the Mexican Market

Abstract: Not only was Digital Transformation (DT) accelerated by the COVID-19 pandemic, but over recent years some companies have already developed actions related to DT. It is well known that DT has many benefits, such as improving business models, making communication channels more efficient and facilitating decision-making. Furthermore, amongst others, one big challenge of DT is to contribute to areas related to sustainability. The objective of this article is to offer an exploratory review of how a small sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 51 publications
(63 reference statements)
1
16
0
Order By: Relevance
“…Pre-COVID-19 [21][22][23][24][25][26][27] During COVID-19 [10][11][12]14,[16][17][18][21][22][23][24] Post-COVID-19 [14,24,39,66,75,[78][79][80] Studies on the pandemic period are of great importance as they provide insight into how the pandemic has affected different aspects of society. The studies mentioned above highlight some key areas that have been the focus of research during the pandemic, including price changes [32,36,38,65], policy implications [40,48,49,55], food safety [17,30,43], and consumer behaviors [12,71,81].…”
Section: Phase Of Covid-19 Authorsmentioning
confidence: 99%
“…Pre-COVID-19 [21][22][23][24][25][26][27] During COVID-19 [10][11][12]14,[16][17][18][21][22][23][24] Post-COVID-19 [14,24,39,66,75,[78][79][80] Studies on the pandemic period are of great importance as they provide insight into how the pandemic has affected different aspects of society. The studies mentioned above highlight some key areas that have been the focus of research during the pandemic, including price changes [32,36,38,65], policy implications [40,48,49,55], food safety [17,30,43], and consumer behaviors [12,71,81].…”
Section: Phase Of Covid-19 Authorsmentioning
confidence: 99%
“…The studies highlight the importance of including sustainability in the organizational culture, which directly influences sustainability through DX [80,81]. Therefore, MSMEs should adopt a vision that promotes sustainable DX to benefit the company, society, and the environment in their organizational culture.…”
Section: Organizational Culturementioning
confidence: 99%
“…The most crucial implication for any organization is to ensure that stakeholders are well-informed about new policies and changes in business operations, particularly during times of crisis [81,110]. By sharing information through digital or physical means, stakeholders can actively contribute to crisis management [108].…”
Section: Crisis Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature has explored the relationship between digital investment and enterprise value, yet no consensus has been reached. Some studies have shown that digital transformation not only positively influences profitability and organizational performance (Chouaibi et al, 2022;Truant et al, 2021;Zeng et al, 2022) but also plays a significant role in creating value, efficiency, and sustainable development of firms (Amit and Han, 2017;Diaz and Montalvo, 2022;Vrontis et al, 2022). A study conducted by Ma et al (2022) indicates that the utilization of digital technology can enhance enterprise value through technological and business model innovation.…”
Section: Introductionmentioning
confidence: 99%